2018
DOI: 10.1111/dme.13669
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of high‐ and low‐risk individuals in the PRIORITY study: urinary proteomics and mineralocorticoid receptor antagonism for prevention of diabetic nephropathy in Type 2 diabetes

Abstract: In this population of individuals with Type 2 diabetes and normoalbuminuria, traditional diabetic kidney disease risk factors differed slightly between participants at high risk and those at low risk of diabetic kidney disease, based on CKD273. These data suggest that CKD273 may provide additional prognostic information over and above the variables routinely available in the clinic. Testing the added value will be subject to our ongoing study. (European Union Clinical Trials Register: EudraCT 2012-000452-34 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…In a second step, the “high risk” patients are randomized to spironolactone or placebo to test the hypothesis that it will be possible to prevent or delay the progression to microalbuminuria. The study population from 15 centers consists of 1777 patients of which 218 are “high risk” and have undergone randomization (Figure ) . The study is funded by the EU and is expected to report in 2019 and, being a prospective randomized study, will be a crucial step in the validation of urinary proteomics in this population both as a predictor of outcome and as well as a potential guide to intervention.…”
Section: Trials Using Urinary Proteomics For Patient Selection and Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second step, the “high risk” patients are randomized to spironolactone or placebo to test the hypothesis that it will be possible to prevent or delay the progression to microalbuminuria. The study population from 15 centers consists of 1777 patients of which 218 are “high risk” and have undergone randomization (Figure ) . The study is funded by the EU and is expected to report in 2019 and, being a prospective randomized study, will be a crucial step in the validation of urinary proteomics in this population both as a predictor of outcome and as well as a potential guide to intervention.…”
Section: Trials Using Urinary Proteomics For Patient Selection and Thmentioning
confidence: 99%
“…They concluded that prospectively collected data is needed and that added value to available clinical information has to be demonstrated. It is clear the PRIORITY study will provide the hitherto most comprehensive and prospective test of the concept, both for the selection of patients at risk and for the provision of early pharmaceutical intervention. Interpretation of the results will also help in the health economy considerations associated with widespread use and implementation as the testing is not without significant cost and will have to be balanced by significant future savings on diabetes‐related morbidity.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition, when perusing the 42 trials, it is observed that the combinatorial use of multiple biomarkers in the form of stratification/diagnostic/prognostic panels is gradually gaining popularity over the evaluations based on single/few biomarkers. For example, the stratification classifier CKD273 in PRIORITY and the prognostic classifiers HF1 and HF2 in uPROPHET consist of 273, 85, and 671 urinary peptides, respectively, while the diagnostic panel in SpecTRA utilizes 16 and 141 proteomic biomarkers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the ongoing Phase II/III PRIORITY study, a classifier based on urinary peptides was used to stratify 1777 patients with type 2 diabetes and normoalbuminuria, so that those at a higher risk of developing nephropathy can be randomized to spironolactone treatment (NCT02040441) . The classifier (CKD273) consists of 273 urinary peptides measured by capillary electrophoresis (CE) coupled with mass spectrometry (CE‐MS) and has demonstrated the capability to detect diabetic nephropathy at a very early stage .…”
Section: Protein Biomarkers In Clinical Trialsmentioning
confidence: 99%
“…The aims of the PRIORITY study were (I) to test CKD273 prospectively as predictive of development of microalbuminuria (primary end-point), and (II) to evaluate in subjects with a high-risk score whether intervention with spironolactone can reduce the risk of microalbuminuria. Traditional diabetic disease risk factors differed slightly between participants at high risk and those at low-risk of disease progression based on the CKD273 score, suggesting that the classifier may provide additional prognostic information over and above the clinical data [39]. Results of the trial have been presented very recently [40].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%